Gastrointestinal Manifestations in Patients with Dengue fever: an observational study - Neupane, Pradeep; Maharjan, Bigyan; Kumar Yadav, Roshan; Shah, Leeza; Subedi, Suraj; Maharjan, Rabin; Kumar Ranjan, Mukesh (Journal of Chitwan Medical College, 2024)
Background: Dengue fever is an arthropod borne viral disease with multisystem involvement and varied clinical presentation. This research work aimed at studying the spectrum of gastrointestinal (GI) manifestations in patients with dengue fever. Method: This was a prospective observational study in which hospitalized adult patients with dengue fever in Chitwan Medical College, Nepal were consecutively enrolled from August to December 2023. Ethical approval was obtained. Clinical presentation, laboratory findings and outcomes were recorded. Gastrointestinal manifestations included symptoms (pertaining to GI tract, hepatobiliary and pancreas), laboratory and imaging findings. Warning sign and features predictive of severe form of dengue were analyzed. Data analysis was done using SPSS version 20. Result: Out of 119 dengue patients, females were 63(53%), 44(37%) had warning signs and 10(8.4%) had severe dengue. At least one gastrointestinal and/or hepatic manifestation was present in 110(92.4%) and at least one gastrointestinal symptom in 92(77.3%) patients. The most common gastrointestinal manifestations were nausea (68.9%), vomiting (56.3%), pain abdomen (25.2%), diarrhea (15.1%), and melena (<1%). Hypertransaminasemia (79.8%) was the most common laboratory abnormalities followed by jaundice (5.0%), hepatomegaly (5%), and splenomegaly (5%). There was one mortality. Multivariate analysis showed vomiting and pain abdomen were two features that were predictive of severe form of dengue. Conclusion: Gastrointestinal manifestations were common (92.4% of 119) in dengue fever, and in this study abdomen pain and vomiting were predictive of severe dengue.